Enhancing Performance of GaAs Photodiodes via Monolithic Integration of Self‐Formed Graphene Quantum Dots and Antireflection Surface Texturing. Issue 3 (27th January 2021) - Namiki, Shunya; Huang, Hsien-Chih; Soares, Julio; Wu, Xihang; Kim, Jeong Dong; Jiang, Bill; Srikumar, Vaanchit; Li, Xiuling
Abstract : III–V semiconductor‐based photodiodes with graphene incorporated have been studied in recent years due to the attractive optoelectronic properties of graphene, including optical transparency and enhanced photoresponsivity. The photoresponsivity can be further improved by converting the semiconductor surface into a 3D antireflection (AR) structure. However, difficulties in transferring graphene on top of structured surfaces degrade the interfacial quality and limit their photoresponsivity. Herein, a high‐performance GaAs photodiode structure with self‐embedded graphene quantum dot (GQD) and simultaneously formed periodic AR 3D surface texturing is reported, all produced by a one‐step wet etching process in a solution of hydrogen fluoride (HF) and potassium permanganate (KMnO4 ) using graphene as a transparent mask. Compared with the planar counterpart without graphene, the photodiodes demonstrated here show an enhancement of photocurrent by 22 times, photoresponsivity by 25 times, and normalized photocurrent to dark current ratio by approximately two orders of magnitude. The improved photoresponsivity of 9.31 mA W −1 is attributed to the increased absorption from AR texturing and the enhanced heterointerface carrier transfer from GQDs to GaAs. This simple, clean yet effective method enables the monolithic incorporation of graphene and graphene‐derived materials on 3D semiconductor structures for applications across a wide range of wavelengths. Abstract : Graphene quantum dot (GQD)‐enhanced GaAs photodiodes are fabricated througha one‐step wet etching process in a solution of HF and KMnO4 to simultaneously convert graphene into GQDs and generate GaAs 3D antireflection structure arrays with smooth sidewalls. The 3D graphene/GaAs photodiode demonstrates a photoresponsivity enhancement of 25 times compared with the planar counterpart.